Studi Literatur Pemanfaatan Sistem Informasi Akuntansi Berbasis Cloud pada UMKM dalam Meningkatkan Efisiensi Pencatatan Keuangan - Latifah Hanum Meilany; Nadya Prananda; Sarah Agustin Siahaan; David Efendi (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, yet many still encounter challenges in manual bookkeeping that is time-consuming, error-prone, and inefficient. The advancement of technology introduces cloud-based accounting systems as a solution to improve the efficiency of financial recording. This study aims to analyze the utilization of cloud accounting by MSMEs in enhancing speed, accuracy, transparency, and accessibility of financial data. The research method employed is a literature review of publications from 2020 to 2025 obtained from Google Scholar, SINTA, Garuda, and MDPI, with content analysis techniques through identification, categorization, and synthesis. The findings reveal that cloud accounting accelerates the recording process, reduces errors, and improves transparency and accountability of financial reports, although challenges such as digital literacy, subscription costs, and data security remain significant. Therefore, the adoption of cloud-based accounting systems is considered a strategic necessity for MSMEs in the digital era, while future research is recommended to conduct empirical case studies on MSMEs using cloud accounting.